SOCIAL MEDIA INFLUENCER, BRAND AWARENESS, AND PURCHASE DECISION AMONG GENERATION Z IN SURABAYA - Fransisca Andreani; Leonardo Gunawan; Selden Haryono (Jurnal Manajemen dan Kewirausahaan, 2021)
Many restaurants and cafes use Social Media Influencer (SMI) services to promote their products/ services. The three dimensions of SMI include reach, relevance, and resonance; and these can influence brand awareness and purchase decision of generation Z consumers. This study involved 108 respondents and used SPSS and Partial Least Square (PLS) as data analysis techniques. The results of this study indicate that reach, relevance and resonance of SMI have positive and significant influences on brand awareness. Reach has positive but insignificant influence on purchase decisions; whereas, relevance and resonance have positive and significant influences on purchase decision. Finally, brand awareness has positive but insignificant influence on purchase decision of Generation Z to restaurants and cafes in Surabaya.